An Unusual Case of Collagenous Gastritis: Incidental Finding in a Patient Presenting with Dysphagia - Chiu-Hsiang Liao; Maruf Saddik; Stephen Ip (Case Reports in Gastrointestinal Medicine)
Collagenous gastritis is a condition characterized by subepithelial deposition of collagen in the gastric mucosa. This condition is rare, with less than 100 cases reported in the literature. Patients with collagenous gastritis typically present with pain or diarrhea. Here, we present a case of a young woman with dysphagia who was found to have esophageal webs and an incidental finding of diffuse gastritis with a cobblestone appearance of the mucosa on endoscopy. Subsequent histology demonstrated features of collagenous gastritis, including mucosal inflammatory infiltrates and collagen deposition. This is one of the few case reports of incidental collagenous gastritis and highlights the importance of judicious use of biopsies.